(untitled) (Global Journal of Science Frontier Research, 2024)
Introduction-Half-silvering Dimensions" E ach dimension having a distinctive boundary called a "Halfsilvering" that acts like a two-way mirror. This means that beings or objects existing in a Higherdimensional space can look down into lowerdimensional spaces but cannot see or perceive the higher-dimensional spaces above them. For example, entities in 3D can observe and interact with 3D, 2D, and 1D, but they cannot see or comprehend dimensions beyond 3D.